The White Male as Narrative Axis in Mayra Santos-Febres’s Nuestra señora de la noche - Helene C. Weldt-Basson (Studies in 20th & 21st Century Literature, 2013)
Mayra Santos-Febres’s 2006 novel, Nuestra señora de la noche, is based on the life of the Puerto Rican madam, Isabel la Negra, a legendary figure in Puerto Rican culture. Using both Mervin Alleyne’s theory of racial discrimination and Aída Hurtado’s theory of racially-based gender discrimination, which shows how the reactions of white and black females are governed by their relation of dependency on or rejection by the white male, this study illustrates how the character Isabel la Negra evolves as a postmodern, feminist character who opposes racism and gender subordination in Puerto Rico through her role as a prostitute. Conversely, the study also illustrates how madness, associated with both white (Cristina Rangel) and black (Montse) females in the novel, is a powerless rather than feminist strategy, into which women descend due to their mistreatment by patriarchal society. The study illustrates how Fernando Fornarís, the white male protagonist, serves as the narrative axis for the development of women’s polarized reactions to patriarchal domination in the novel.
Keywords: Mayra Santos-Febre; Nuestra señora de la noche; Isabel la Negra; Puerto Rico; Puerto Rican culture; white male; feminine literature; dependency; feminist character; patriarchy